UNIDA AR-Book: Interactive Virtual Application of Darussalam Gontor Campus Putri University Based On Augmented Reality - Faisal Reza Pradhana; Dihin Muriyatmoko; Fulki Rusyda (Universitas Muhammadiyah Sidoarjo, 2021)
Darussalam Gontor University is a newly established campus with fairly rapid infrastructure development. The design of the prototype building using a brochure owned by UNIDA Gontor Putri is considered unable to visually represent the buildings that have been or will be built properly. This study aims to implement Augmented Reality Book (AR-Book) technology as an introduction media and a tool for the layout of campus buildings, as well as a medium for documentation or archives that can be stored in the long term. Building data is obtained from observations by collecting data by observing directly at the location and visualizing in the form of photos or videos taken using cameras and drones. This media is based on android mobile using marker based augmented reality technology to visualize the 3-dimensional shape of the created building object. Media is built following the stages of the Software Development Life Cycle (SDLC) model. Testing is carried out through functional testing of the application using the blackbox method to test the overall function of the features in the application so that it can run well, testing the level of suitability of the application with android devices. The blackbox test results show that all features are functioning properly and there are no errors. Subsequent research this media can be developed into the form of a campus tour by utilizing virtual reality technology.